A controlled intervention to increase participation in cardiac rehabilitation. (September 2015) - Dankner, Rachel; Drory, Yaakov; Geulayov, Galit; Ziv, Arnona; Novikov, Ilya; Zlotnick, Amnon Y; Moshkovitz, Yaron; Elami, Amir; Schwammenthal, Ehud; Goldbourt, Uri
Background: Cardiac rehabilitation programs are greatly underutilized. Design: This study was a multicenter interventional controlled cohort study. Methods: From cardiothoracic departments of five medical centers, 520 coronary artery bypass graft (CABG) patients (386 men) were enrolled in the control arm and 504 CABG patients (394 men) in the intervention arm of our study. A 1-hour seminar to medical staff on the benefits of cardiac rehabilitation followed the control phase and preceded the intervention phase. Patients in the intervention arm received written and oral explanations on cardiac rehabilitation benefits and eligibility, and a follow-up telephone call 2 weeks after hospital discharge. Patients in both study arms were interviewed in the hospital prior to CABG surgery and in their homes a year later. Results: Rates of participation in cardiac rehabilitation were 16.5% (86/520) for the control arm and 31.0% (156/504) for the intervention arm ( p < 0.001). Factors strongly associated with participation in cardiac rehabilitation were: belonging to the intervention arm (OR: 2.06 95% CI: 1.46–2.90, p < 0.0001), male sex, average or above average income, sports related physical activity before surgery, younger age and BMI > 30 kg/m 2 . Particularly high increases in participation rates following the implementation were observed among subpopulations of 10 years or less education and those reporting below average income. "Lack of knowledge" regarding cardiac rehabilitation was the reason most commonly stated for not participating in a cardiac rehabilitation program. Conclusion: Participation in cardiac rehabilitation almost doubled following a low cost intervention with significant effects on subpopulations that have been underrepresented in cardiac rehabilitation programs.